2008
DOI: 10.1055/s-2007-965672
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Definitive Peritoneal Drainage for Spontaneous Intestinal Perforation in Extremely Low Birth Weight Neonates

Abstract: Peritoneal drainage for spontaneous intestinal perforation in ELBW neonates is more likely to be definitive in the absence of bandemia and vasopressor requirement. These may be important factors in deciding whether to proceed to laparotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
(62 reference statements)
0
11
2
Order By: Relevance
“…This percentage is higher than the studies by Moss et al 27 and Rees et al, 28 who showed definitive PD rates of 62 and 26%, respectively. When comparing our study to a recent and similar (although smaller sample size) study looking at SIP patients treated with PD by Emil et al, 26 the difference is striking. Their rate of definitive PD was only 31% (5/16).…”
Section: Discussionmentioning
confidence: 40%
See 3 more Smart Citations
“…This percentage is higher than the studies by Moss et al 27 and Rees et al, 28 who showed definitive PD rates of 62 and 26%, respectively. When comparing our study to a recent and similar (although smaller sample size) study looking at SIP patients treated with PD by Emil et al, 26 the difference is striking. Their rate of definitive PD was only 31% (5/16).…”
Section: Discussionmentioning
confidence: 40%
“…Numerous variables can and will influence the success rate of PD, including the preferences and biases of attending pediatric surgeons and neonatologists. Some groups or practices will have a low threshold for reoperation as in the studies by Rees et al 28 and Emil et al, 26 whereas others will wait longer to intervene. At our institution, when a peritoneal drain is placed in an infant suspected to have SIP, it is done with the hope that it will be a definitive therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients treated solely with a drain, the diagnosis of SIP is challenging for some investigators. 5 It should also be noted that only 37% of infants in the study had pneumatosis intestinalis and 27% of the 'progressors' who were 2 weeks old or less never received enteral nutrition. Both features suggest that a significant portion of this population might have had SIP with pneumoperitoneum (unfortunately these data are not provided).…”
mentioning
confidence: 89%